Diffusion profiles in L. lactis biofilms under different conditions. Issue 1 (10th November 2020) - Chodorski, Jonas; Hauth, Jan; Strieth, Dorina; Wirsen, Andreas; Ulber, Roland
Abstract: Despite being an important topic in biofilm research, we still know little about diffusion in biofilms. Emerging biofilms of Lactococcus lactis growing in custom‐made flow‐cells were monitored and diffusion constants across the height of the biofilms recorded. The biofilms showed different diffusional behavior with regard to flow rate and pH variations, despite growing to similar thickness. At a higher flow rate, the biofilm exhibits slower diffusion compared to the reference cultivation at lower flow rate. By increasing pH, the biofilm exhibited fast growth and little difference in diffusion compared to the reference cultivation. Furthermore, the diffusion inside of the biofilms differed depending on the position in the flow‐cell. The present study reveals new insights in how external factors can affect structure and density of biofilms. The method can be reliably used for L. lactis biofilms with a thickness up to 120 μm.